Effects of Drought Stress on Photosynthetic Characteristics and Endogenous Hormone Levels in the Sweet Potato (Ipomoea batatas) - Shihao Huang; Jinqiang Wang; Huanyuan Wang; Huan Li (Horticulturae)
In the context of climate change and severe water shortages in agriculture, we explored water stress responses in the sweet potato (Ipomoea batatas) in terms of endogenous hormone levels and other physiological characteristics, providing a theoretical basis for drought-resistant cultivation of sweet potato. This study was conducted from 2021–2022 in a solar greenhouse under artificially controlled water conditions. We determined biomass, agronomic indexes, photosynthetic parameters, and endogenous hormone levels in three treatments: normal water supply (CK), mild drought (LD), and severe drought (HD). The results revealed that drought stress inhibited aboveground and belowground sweet potato growth compared with CK; sweet potato yield decreased with increasing drought. The net photosynthetic rate, stomatal conductance, and transpiration rate of sweet potato leaves decreased significantly under drought stress. The leaves’ intercellular CO2 concentration (Ci) decreased with increasing drought up to 50 days after transplanting but increased with increasing drought up to 75 days after transplanting. The zeatin riboside (ZR) and indole-3-acetic acid (IAA) contents were significantly lower in sweet potato leaves and tubers in the LD and HD treatments compared with CK, whereas the abscisic acid (ABA) content was significantly higher. Within the same period, the (ZR + IAA)/ABA ratio decreased with increasing drought severity. Correlation analysis revealed that the ABA and leaf Ci were significantly positively correlated, and both indices were significantly negatively correlated with all other indices. Aboveground dry weight was significantly correlated with the ZR and IAA contents. These findings demonstrate the regulatory effects of elevated leaf ABA concentrations on stomatal conductance during drought and indicate that stomatal closure was mainly responsible for the decreased photosynthetic rate observed in the early stage of drought. The rapid decrease in the photosynthetic rate in the late stage of drought may have been caused by non-stomatal factors. These findings provide a theoretical foundation for future drought-resistant sweet potato cultivation.